Predictors of pathological response and clinical outcome following chemoradiation for locally advanced rectal cancer - a systematic review - Amaral,Erica (2020)
Abstract Background: Colorectal cancer is one of the most common types of cancer and is associated with a high lethality rate. Treatment is multidisciplinary, and neoadjuvant chemoradiation is recommended in locally advanced rectal cancer. About 15% of patients answer favorably to neoadjuvant chemoradiation, so it is important to determine the predictors of response. Objective: To review the results of studies that analyzes the predictors of complete pathological response to neoadjuvant chemoradiation in patients with locally advanced rectal cancer. Search methods: We searched for eligible articles in data bases Pubmed and Scopus, between the 12th and the 20th of March 2020. The following key words were used: “predictors of response”, “chemoradiation” and "locally advanced rectal cancer". Selection criteria: Inclusion criteria: Studies including patients with locally advanced rectal cancer, patients receiving neoadjuvant chemoradiation as treatment, studies including predictors of response to neodjuvant chemoradiation, overall survival as an outcome and regarding language restrictions, only articles in English were accepted, only studies published until the 31st of December 2019 were accepted. Main results: Fourteen studies fulfilled the inclusion criteria. Thirteen are cohort studies and one is a clinical trial. Four groups of predictors were defined: blood markers, tumors, histopathological and patients’ characteristics. Author's conclusions: During the analysis of the articles, there were several predictors identified as potential candidates for clinical practice, such as high pre neoadjuvant chemoradiation Carcinoembryonic Antigen levels and small post neoadjuvant chemoradiation tumor size. Nevertheless, it is difficult to make definitive conclusions about the most reliable predictors. That is why it is crucial to initiate further studies with standardized cut-off values and a methodology homogenization.